Physical characteristics of agricultural waste decomposition using different bio-activators - Muliatiningsih, Muliatiningsih (Protech Biosystems Journal, 2023)
This study aims to determine the physical characteristics of agricultural waste decomposed with different bio-activator sources. The method used in the research is an experimental method using a one-factor Completely Randomised Design, namely the source of Bio-Activator with 4 (four) treatments, namely B0: Commercial EM 4, B1: PGPR bamboo, B2: MOL, B3: Coconut water.  Each treatment was repeated 3 times so that 12 experimental units were obtained. The parameters observed included moisture content, biomass weight change, temperature and compost colour. The research was conducted in the Greenhouse of the Faculty of Agriculture, Muhammadiyah Mataram University. The data obtained were statistically analysed using Analysis of Variance at the 5% level. Treatment results that have a significant effect will be continued with the BNJ test at the 5% level. The results showed that the temperature value, the final weight of compost and the percentage difference in compost weight were not significantly different in all treatments.